1978
DOI: 10.4319/lo.1978.23.3.0401
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dispersion of benthic Foraminifera in the abyssal central North Pacific 1

Abstract: Five 0.25‐m2 box cores (four open cores and one vegematic core subdivided in situ into 25 contiguous 10‐ × 10‐cm subcores) reveal that populations of benthic agglutinated Foraminifera in the central North Pacific are extremely abundant and diverse. As many as 120 species and 10,310 total fragments occur in a single open core, and the Foraminifera outnumber all metazoan taxa combined by at least an order of magnitude. Significant patchiness occurs on both the between‐core scale of kilometers and the within‐core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 19 publications
(9 reference statements)
3
40
0
Order By: Relevance
“…Observations on population densities in the central North Pacific (Hessler & Jumars 1974, Bernstein et al 1978, Snider et al 1984 and in the Northeast Pacific at Stn M (Drazen et al 1998) have shown the numerical importance of benthic foraminifera among the sediment-inhabiting fauna in this region, indicating their important contribution to carbon cycling here. Especially monothalamous soft-walled foraminifera are important components of deep-sea sediments (Gooday 1994), in particular in oligotrophic areas and below the carbonate compensation depth with an assumed diet of refractory organic material and bacteria (Gooday et al 2008).…”
Section: Introductionmentioning
confidence: 86%
“…Observations on population densities in the central North Pacific (Hessler & Jumars 1974, Bernstein et al 1978, Snider et al 1984 and in the Northeast Pacific at Stn M (Drazen et al 1998) have shown the numerical importance of benthic foraminifera among the sediment-inhabiting fauna in this region, indicating their important contribution to carbon cycling here. Especially monothalamous soft-walled foraminifera are important components of deep-sea sediments (Gooday 1994), in particular in oligotrophic areas and below the carbonate compensation depth with an assumed diet of refractory organic material and bacteria (Gooday et al 2008).…”
Section: Introductionmentioning
confidence: 86%
“…There were also some significant differences in the abundance and variance of species in the total populations (Tables 7 to 9). Patchy distributions of benthic foraminiferal populations are well documented in both shallow water (Buzas 1968, 1970, Lee et al 1969, Matera & Lee 1972, Bernhard 1987, Hohenegger et al 1989) and the deep-sea (Bernstein et al 1978, Bernstein & Meador 1979, Kaminski 1985. Such spatial heterogeneity may have contributed to at least some of the differences observed between the April and July assemblages.…”
Section: Phytodetritus Populationsmentioning
confidence: 96%
“…Habitat partitioning --A number of studies have suggested microhabitat partitioning as an important factor for the maintenance of diversity in deep sea benthic communities (Jumars, 1975;Bernstein et al, 1978). Under equilibrium conditions, species which do not share the same microhabitat do not compete with one another, and the diversity of the community can be maintained at high levels.…”
Section: Panama Basin Aii 112 Spade Core 9 Live/dead Individualsmentioning
confidence: 99%